Evaluation of eastern gamagrass using the beef N.R.C. model - Meredith, Alisa Kaye (Kansas State University, 2008)
Currently there are no model inputs for eastern gamagrass [Tripsacum dactyloides (L.) L] for use in the National Research Council's (NRC) beef cattle model. This study was conducted to determine model inputs for two eastern gamagrass varieties for use with the forage database of the NRC model. Cattle producers in the Midwestern US will be able to evaluate eastern gamagrass in a forage system and estimate net energy for maintenance (NEm), metabolizable protein (MP), and degradable intake protein (DIP) balance for various production scenarios. Eastern gamagrass varieties 'Iuka' and 'Pete' were arranged in a split-plot randomized complete block experiment with four replications. Varieties were whole plots with harvest maturities as split plots. Plant tissue was harvested from both varieties at four maturities: vegetative/early elongation, anthesis, seed shattering and dormancy. Various compositional attributes were determined on forage samples to enable the determination of model inputs for predicting energy and protein balances. A slight difference between varieties was found for crude protein concentration (p<0.05). Differences (p<0.05) due to maturity were found for all analyses used in the model, corroborating the decline in nutritive value of eastern gamagrass with advancing maturity. Neutral detergent fiber (NDF) ranged from 593 g kg-1 at the vegetative/early elongation stage of maturity to 731 g kg-1 at dormancy. Assumed animal and environmental inputs were used for beef cattle at two stages: nonlactating 160 d prepartum and 60 d peak lactation. Energy and protein balance were estimated using level I of the model. The vegetative/early elongation stage of development supplied the greatest amount of MP. Digestible intake protein declined as plant tissue matured. All but the vegetative/early elongation stage of maturity were limited in DIP for cows in both stages of production. Soybean meal was used as a protein supplement in amounts ranging from 0.8 kg to 1.4 kg to meet nutritional demands of cattle grazing eastern gamagrass at anthesis, seed shattering and dormancy. In the simulations conducted, eastern gamagrass would be an acceptable forage source for beef cattle provided that appropriate protein supplementation was given when the forage was at more advanced stages of maturity.
Keywords: NRC Beef Model; Eastern gamagrass; Tripsacum dactyloides; Nutrient Requirements for Beef Cattle; Agriculture, Agronomy (0285); Agriculture, Animal Culture and Nutrition (0475)